DEVELOPMENT Pengembangan Sistem Brooder Berbahan Dasar Uap Bensin sebagai Upaya Menekan Biaya Operasional Budi Daya Ayam Broiler - Kurriawan Budi Pranata; Tri Ida Wahyu Kustyorini; Muhammad Priyono Tri Sulistyanto; Muhammad Ghufron; Sholikhan Sholikhan; Djoko Adi Susilo (Institut Pertanian Bogor, 2021)
Broiler chicken is one of popular alternative source of protein for local people in Indonesia due to the low price and good quality meat. However, broiler breeders unable obtain enough income because face high operating costs due to the animal feed and high consumption of LPG gas in the Day Old Chick (DOC) brooder process. During 15 days brooder DOC process, at least 36 kg/day of LPG gas is consumed for 3000 chicks. Therefore, the purpose of this community service activity is to reduce brooder DOC operational costs for broilers through research, development and implement an alternative heaters using gasoline vapor vaporization. Community service activities are carried out with six stages of activity, namely 1. Real identification of the brooder process in the field 2. Factor analysis using a causes and effects table 3. Improvement of brooder management procedures 4. Conduct an alternative low cost brooder design 5. Investigation of the fabricated brooder sistem and 6. Analysis of the results of the change impact test. The results of the high operational cost DOC process investigation are tight less of the brooder DOC curtain cage, uncontrolled the intensity of the flames, and unfixed of LPG price. The new procedure proposed is fixing the brooder DOC curtain cage, new setting intensity of the flames in day and night, and using an alternative low cost brooder design to avoid unfixed LPG gas price. The proposed procedure is able to reduce brooder operational costs by up to 50%.